Human Nature and Characteristics in the Perspective of Islamic Education: A Review of al-Qur'an and al-Hadith - Ridha Aulia; Muhammad Hafidz Khusnadin; Muhammad Raja Iqbal Fahri; Jimmy Malintang; Yazid Imam Bustomi (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Humans as creatures created by Allah Swt. who are endowed with perfection in the form of reason and potential that is not given to other creatures. There are various terms in the Qur'an that refer to humans, such as insan, an-nas, al-basyar, and al-ummah, which reflect the duties and characteristics of humans according to their potential. The search for human nature is endless, because it has been a topic of discussion throughout history, with various philosophical and scientific perspectives. Therefore, this study aims to examine the nature of man in the perspective of the Qur'an and Hadith and its relevance to education. By using a qualitative approach and literature research method. This research provides an understanding of the nature of man that is based on terms in the Qur'an and Hadith and its role in the world of education. Human nature involves fitrah, natural potential, and character development, confirming the importance of education in optimizing human potential as a creature given a noble task by Allah SWT.